Bruno Caseirão, O essencial sobre Viana da Mota (Lisboa, INCM, 2020), 116 pp., ISBN: 978-972-27-2828-7 - Artiaga, Maria José (Revista Portuguesa de Musicologia, 2021)
Recensão: Bruno Caseirão, O essencial sobre Viana da Mota (Lisboa, INCM, 2020), 116 pp., ISBN: 978-972-27-2828-7